Estimation of Direct Healthcare Costs of Fungal Diseases in the United States. (10th September 2018) - Benedict, Kaitlin; Jackson, Brendan R; Chiller, Tom; Beer, Karlyn D
Abstract: Background: Fungal diseases range from relatively-minor superficial and mucosal infections to severe, life-threatening systemic infections. Delayed diagnosis and treatment can lead to poor patient outcomes and high medical costs. The overall burden of fungal diseases in the United States is challenging to quantify, because they are likely substantially underdiagnosed. Methods: To estimate the total, national, direct medical costs associated with fungal diseases from a healthcare payer perspective, we used insurance claims data from the Truven Health MarketScan 2014 Research Databases, combined with hospital discharge data from the 2014 Healthcare Cost and Utilization Project National Inpatient Sample and outpatient visit data from the 2005–2014 National Ambulatory Medical Care Survey and the National Hospital Ambulatory Medical Care Survey. All costs were adjusted to 2017 dollars. Results: We estimate that fungal diseases cost more than $7.2 billion in 2017, including $4.5 billion from 75055 hospitalizations and $2.6 billion from 8993230 outpatient visits. Hospitalizations for Candida infections (n = 26735, total cost $1.4 billion) and Aspergillus infections (n = 14820, total cost $1.2 billion) accounted for the highest total hospitalization costs of any disease. Over half of outpatient visits were for dermatophyte infections (4981444 visits, total cost $802 million), and 3639037 visits occurred for non-invasive candidiasis (total cost $1.6 billion). Conclusions: Fungal diseases impose a considerable economic burden on the healthcare system. Our results likely underestimate their true costs, because they are underdiagnosed. More comprehensive estimates of the public health impact of these diseases are needed to improve their recognition, prevention, diagnosis, and treatment. Abstract : To provide insight into the burden of fungal diseases in the United States, we used several administrative data sources to estimate their total direct healthcare costs. We estimate that fungal disease healthcare costs exceed $7 billion annually.